Effects of maternal anthropometrics on pregnancy outcomes in South Asian women: a systematic review*. (19th January 2018) - Slack, E.; Rankin, J.; Jones, D.; Heslehurst, N.
Summary: Aim: This systematic review investigates associations between maternal pre‐pregnancy/early‐pregnancy anthropometrics (e.g. weight and body fat), anthropometric change and pregnancy outcomes in South Asian and White women. Methods: Twelve electronic literature databases, reference lists and citations of all included studies were searched. Observational studies published in the English language were included. Descriptive synthesis was used to summarize the evidence base. Results: Twenty‐two studies met the inclusion criteria (403, 609 births [351, 856 White and 51, 753 South Asian]). Nine were prospective cohort studies, nine were retrospective cohort studies and two were cross‐sectional studies. Results suggested that in South Asian women, maternal pre‐pregnancy/early‐pregnancy anthropometrics were associated with anthropometric change, birthweight, mode of delivery and gestational diabetes mellitus (GDM). Gestational anthropometric change was found to be associated with GDM. There was limited evidence to suggest that there may be associations between maternal pre‐anthropometrics/early anthropometrics and hypertensive disorders, stillbirth, congenital anomalies, post‐natal weight retention and post‐natal impaired glucose tolerance. The evidence suggested a combined effect of pre‐pregnancy/early‐pregnancy anthropometrics and gestational anthropometric change on both GDM and post‐natal weight retention. Conclusion: The increased risk of adverse pregnancy outcomes in South Asian women should be considered in guidelines for weight management before and during pregnancy.